2003
DOI: 10.3354/meps254199
|View full text |Cite
|
Sign up to set email alerts
|

Pre-emptive competition as a selective pressure for early reproduction in the polychaete Nereis virens

Abstract: Reproduction in the semelparous polychaete Nereis virens occurs at a time of year when seawater temperatures are lower than the optimum temperatures for fertilization and larval development and at a time when seawater temperatures are rising. This study assesses the possible role of intra-specific competitive interactions between settling N. virens post-larvae as a selective pressure for 'early' reproduction. A series of laboratory competition experiments were conducted between 2 cohorts of N. virens post-larv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Lewis et al (2003) found this protocol to have no impact on survivorship. Sediment was passed though the 100 µm sieve and the settled larvae were recorded as dead or alive as described above.…”
Section: Effects Of Copper-spiked Sediment On Larval Settlementmentioning
confidence: 89%
See 1 more Smart Citation
“…Lewis et al (2003) found this protocol to have no impact on survivorship. Sediment was passed though the 100 µm sieve and the settled larvae were recorded as dead or alive as described above.…”
Section: Effects Of Copper-spiked Sediment On Larval Settlementmentioning
confidence: 89%
“…After 10 min, 7 ml of the overlying solution was replaced three times with 7 ml of pasteurized seawater to reduce the chances of polyspermy. Petri dishes were then covered and maintained at 10EC (LD12:12) for 24 h. The contents of each dish were then fixed with 4% formalin solution in seawater and developmental success was assessed in 50 oocytes as described by Lewis et al (2003).…”
Section: Pre-fertilization Incubation Of Oocytes In Coppermentioning
confidence: 99%
“…Typically, the reproductive strategy of the large-bodied phyllodocid and eunicid polychaetes involves highly synchronised epidemic spawning and there appears to have been strong selection for reproductive precision (Lewis et al, 2002(Lewis et al, , 2003Olive et al, 2001;Watson et al, 2000). Such worms liberate a large mass of gametes that are matured simultaneously to the external environment where fertilisation takes place.…”
Section: Fossil Polychaeta: Implications For Biorhythm Evolutionmentioning
confidence: 97%
“…An analysis of foraging behaviour, however, indicated that all individuals in a population subjected to this environmental cue exhibit a suppression of foraging behaviour (Last and Olive, 1999) in the autumn and must therefore have responded to this environmental cue. Lewis et al (2003) argue that this universal response may be adaptive as it reduces risk. Individuals are less likely to emerge from their burrows after the photoperiodic transition.…”
Section: Introductionmentioning
confidence: 98%